2022
DOI: 10.1126/sciadv.abm2225
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of Odinarchaeota tubulin and the implications for eukaryotic microtubule evolution

Abstract: Tubulins are critical for the internal organization of eukaryotic cells, and understanding their emergence is an important question in eukaryogenesis. Asgard archaea are the closest known prokaryotic relatives to eukaryotes. Here, we elucidated the apo and nucleotide-bound x-ray structures of an Asgard tubulin from hydrothermal living Odinarchaeota (OdinTubulin). The guanosine 5′-triphosphate (GTP)–bound structure resembles a microtubule protofilament, with GTP bound between subunits, coordinating the “+” end … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…These differences could be due to different parameters of the reconstructions (taxonomic sampling, the use of different outgroups, or different methods for the MSA trimming), showing the phylogenetic instability of these prokaryotic tubulins and, therefore, the difficulty in inferring their evolutionary placement. Nevertheless, from our reconstructions, it is clear that OdinTubulins and BtubA/B are closer to α- and β-tubulins, in agreement with recent analyses ( Akıl et al, 2022 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These differences could be due to different parameters of the reconstructions (taxonomic sampling, the use of different outgroups, or different methods for the MSA trimming), showing the phylogenetic instability of these prokaryotic tubulins and, therefore, the difficulty in inferring their evolutionary placement. Nevertheless, from our reconstructions, it is clear that OdinTubulins and BtubA/B are closer to α- and β-tubulins, in agreement with recent analyses ( Akıl et al, 2022 ).…”
Section: Resultssupporting
confidence: 92%
“…Despite the possible incompleteness of the Asgardarchaeota metagenomes, the sequencing of several Asgardarchaeota clades ( Liu et al, 2021 ) confirmed that this OdinTubulin is still uniquely found in this archaeon. In vitro and at high temperatures, this OdinTubulin forms tubules with short curved protofilaments coiling around the tubule circumference, more similar to FtsZ, rather than running parallel to its length as in eukaryotic microtubules ( Akıl et al, 2022 ). Nevertheless, the genome context of this OdinTubulin displays interesting features related to eukaryotes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prokaryotic homologs are called FtsZ, and form structure like a contraction ring in eukaryotes. Recently, we analyzed the tubulin homolog from the archaea Odin, determined the polymerization conditions, and performed cryo-EM analysis [17]. The results were surprising.…”
Section: The Archaea Tubulin Homologmentioning
confidence: 99%
“…(A–D) Scheme of the main conformational changes in tubulin and MTs. ,,, (E) Prokaryotic tubulins described in the manuscript. , …”
Section: Introductionmentioning
confidence: 99%